1 and 2 Samuel - Chisholm, Robert B., author; Strauss, Mark L.; Walton, John H., 1952-; Rosset, rosalie de (Grand Rapids, Michigan : Baker Books, 2013)
"The Teach the Text Commentary Series gives pastors the best of biblical scholarship and presents the information needed to move seamlessly from the meaning of the text to its effective communication. By keeping the discussion in each carefully selected preaching unit to six pages of focused commentary, the volumes allow pastors to quickly grasp the most important information. Each unit of the commentary includes the big idea and key themes of the passage; sections dedicated to understanding, teaching, and illustrating the text; and full-color illustrations, maps, and photos. Robert B. Chisholm Jr.'s volume on the books of 1-2 Samuel provides carefully organized guidance for interpreting, teaching, and illustrating these important historical books."--page 4 of cover
Includes bibliographical references (pages 323-328) and index
Keywords: Commentaries; Commentaries; Commentaries